A quick scoping review of efficacy, safety, economic, and health-related quality-of-life outcomes of short- and long-acting erythropoiesis-stimulating agents in the treatment of chemotherapy-induced anemia and chronic kidney disease anemia. (September 2018) - Arantes, Luiz H.; Crawford, Jeffrey; Gascon, Pere; Latymer, Mark; Launay-Vacher, Vincent; Rolland, Catherine; Scotte, Florian; Wish, Jay
Highlights: A QSR was carried out to define the clinical, economic, and quality of life outcomes for ESAs in patients with CKD-induced anemia or CIA. The evidence suggests little difference in efficacy, quality of life, and safety outcomes among ESA types. Cost-effectiveness and downward pressure on market price are likely to become the main factors driving the choice of agent. Abstract: Erythropoiesis-stimulating agents (ESAs) are man-made forms of erythropoietin used in the treatment of anemia. This quick-scoping review of systematic literature reviews (SLRs) was conducted to define the clinical, economic, and health-related quality of life (HRQoL) outcomes for short-acting and long-acting ESAs in patients with chronic kidney disease–induced anemia (CKD-IA) and patients with chemotherapy-induced anemia (CIA). Embase, Medline, and the Cochrane Database of Systematic Reviews were searched from their establishment until October 2017. SLRs related to the use of short-acting and long-acting ESAs in the treatment of CIA and CKD-IA were included. Forty-eight studies met the inclusion criteria. The evidence suggests little difference in efficacy, HRQoL, and safety outcomes among ESA types. Cost-effectiveness and market price are likely to become determining factors driving the choice of agent. Comparative studies and costing models accounting for the utilization of biosimilars are needed to establish which ESAs are more cost-effective.